Strengthening Mental Toughness through Self-Compassion, Self-Disclosure and Spirituality for Orphanage Adolescents - Aziz, Akbar Nur; Rahmatullah, Azam Syukur; Khilmiyah, Akif (Indigenous, 2023)
This study aims to analyze the influence of self-compassion and self-disclosure through spirituality on the mental health of adolescents living in orphanages. The research method uses survey techniques with a descriptive quantitative approach with a correlational model. The research subjects were obtained from 3 locations, namely Daarut Taqwa Orphanage, Minggir, Sleman DIY., Mafaza Orphanage, Yogyakarta City, DIY., and La Tazhaan Orphanage, Banguntapan, Bantul, DIY. A total of 165 respondents with vulnerable ages 12-18 years. Data collection techniques are carried out by observation, interviews, and research questionnaires. Data analysis technique using SmartPLS version 3 application with secound order embbedded two stages approach. The results of this study show that: 1) There is a positive and significant influence of self-compassion with the mental health of orphanage adolescents, both direct and influence through the medium of spirituality; 2) There was no significant influence between the self-disclosure variable and the mental health of orphanage adolescents directly. However, there is a positive and significant influence between the self-disclosure variable and the mental health of orphanage adolescents through the spirituality mediator variable; 3) There is a positive and significant influence between the spirituality variable and the mental health variable of the orphanage adolescent directly. The implication of this study is that to prevent orphanage adolescents from mental health disorders, it is necessary to strengthen adolescent spirituality consistently and increase self-compassion attitudes in orphanage adolescents.